PROSPECTS FOR THE DEVELOPMENT OF ACCOUNTING IN THE 21ST CENTURY - Lukin, Vladimir; Peniak, Yuliia (European Science, 2025)
The prospects for the development of accounting in the 21st century are investigated. Accounting is considered as a socio-technical system. It is established that the options for the future development of accounting largely depend on the prospects for th